Representations of the Holocaust in Albanian secondary school history textbooks since the Educational Reform of 2004 - Luku, Esilda (Journal of educational media, memory, and society, 2020)
This article examines the extent to and the ways in which the Holocaust is presented in Albanian secondary school history textbooks. It offers a quantitative analysis of the space devoted to the Holocaust in proportion to the textbooks’ overall content and a qualitative content analysis based on the narrative patterns outlined in the UNESCO report The International Status of Education about the Holocaust: A Global Mapping of Textbooks and Curricula. It demonstrates that Albanian textbooks offer scant coverage of the Holocaust, but that some changes regarding the conceptualization, contextualization, and narrative of the Holocaust have been implemented since the curricular reform of 2004.